Using Six Sigma to achieve sustianble manufacturing - Min Zhang; Awasthi, Anjali (Proceedings of the 2014 International Conference on Innovative Design and Manufacturing (ICIDM), 2014)
Sustainability has become a crucial element for the world to generate profit while keeping its citizens to live in a healthy environment. As a key contributor of our society, manufacturing industry not only generates the most profit and employment, but also contributes a lot of violence against human rights and environment. This paper has combined sustainable manufacturing with Six Sigma, which is the most useful tool for continuous improvement, to create a systematical framework for manufacturing practitioners to achieve sustainable manufacturing. This framework has given detailed steps from problem definition to achieving leadership in sustainability in order to maintain the efforts. It also allows engineers to easily adjust this framework based on the specific organizations' situation.